Proceedings of the Fifth Workshop on Refactoring Tools 2012
DOI: 10.1145/2328876.2328884
|View full text |Cite
|
Sign up to set email alerts
|

A language-independent parallel refactoring framework

Abstract: Recent trends towards increasingly parallel computers mean that there needs to be a seismic shift in programming practice. The time is rapidly approaching when most programming will be for parallel systems. However, most programming techniques in use today are geared towards sequential, or occasionally small-scale parallel, programming. While refactoring has so far mainly been applied to sequential programs, it is our contention that refactoring can play a key role in significantly improving the programmabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Current studies have shown that refactoring provided support for the mainstream parallel programming languages and parallel libraries. Brown et al (2012) presented a language-independent parallel refactoring framework that was not limited to a specific language andaimed to improve the programmability of parallel systems by applying well-defined refactoring. This framework leveraged high-level design pattern rewrite rules to introduce parallelism.…”
Section: Results For Rq5mentioning
confidence: 99%
“…Current studies have shown that refactoring provided support for the mainstream parallel programming languages and parallel libraries. Brown et al (2012) presented a language-independent parallel refactoring framework that was not limited to a specific language andaimed to improve the programmability of parallel systems by applying well-defined refactoring. This framework leveraged high-level design pattern rewrite rules to introduce parallelism.…”
Section: Results For Rq5mentioning
confidence: 99%
“…In future work, we intend to explore which programming patterns (e.g., Skeletons [7]) fit within our system.…”
Section: Resultsmentioning
confidence: 99%
“…[2,7]) plus fundamental hylomorphism laws [31]. For example, a parallel pipeline structure ( ) is functionally equivalent to a function composition; a task farm farm can be introduced for any structure; and divide-andconquer dc and feedback fb skeletons can both be derived from hylomorphisms.…”
Section: The Structure-annotated Type Systemmentioning
confidence: 99%